Effect of heparinization on promoting angiogenesis of decellularized kidney scaffolds. Issue 10 (6th April 2021) - Zhou, Lebin; Wang, Zhiyi; Wang, Zhibin; Zhu, Junyi; Feng, Yulu; Zhang, Deming; Shen, Chenfang; Ye, Xiaoting; Zhu, Jieyang; Wei, Peng; Mei, Jin; Zhang, Jianse
Abstract: Native decellularized extracellular matrix provides an adequate platform for tissues and organs and promotes the development of organogenesis and tissue remodeling. However, thrombosis poses a great challenge that hinders the transplantation for a substantial organ in vivo. Therefore, anticoagulation and re‐reendothelialization of organ biological scaffolds are the primary concerns to be addressed before orthotopic transplantation. Herein, a heparinized decellularized kidney scaffold (HEP‐DKSs) was prepared using end‐point attachment technology, followed by binding the vascular endothelial growth factor (VEGF) to greatly improve the hemocompatibility and angiogenesis of DKSs. Based on the anticoagulant, co‐culture of human umbilical vein endothelial cells, and subcapsular transplantation of kidney experiments, HEP‐VEGF‐DKSs are shown to reduce platelet adhesion, which is crucial for subsequent vascularization and slow release of heparin and VEGF, suggesting its ability of improve neovascularization. Taken together, these data indicated an optimal anticoagulation function of HEP‐VEGF‐DKSs and the potential of vascularization for regeneration of whole decellularized kidney. Abstract : Schematics diagram of the structures and process in the DKSs with HEP‐VEGF modified.